Perancangan Sistem Informasi Akuntansi Persediaan Di Blaufabrika Coffe - Yunika Latifatunnufus; Yusli Mariadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to design an inventory accounting information system tailored to the operational needs of Blaufabrika Coffe. The main issue faced by the company is the manual inventory recording process, which hinders the acquisition of accurate and timely information. This research employs a research and development approach with data collection techniques such as observation, interviews, and documentation. The results indicate that the manual system hampers business efficiency, is prone to recording errors, and lacks internal control over inventory. The proposed accounting information system includes the preparation of transaction documents, document flow design, and inventory reporting. This system is expected to improve the effectiveness and efficiency of inventory management and support managerial decision-making